前立腺癌が先行し治療抵抗性間質性肺炎を併発した抗Jo-1抗体陽性多発性筋炎の１剖検例 - 西成田, 進; 早川, 純子; 仁科, 有美子; 金子, 菜穂; 土屋, 貴彦; 青木, 正紀 (臨床リウマチ, 2008)
The patient was a 68-year-old man. He had been diagnosed with adenocarcinoma of the prostate in December 2006 and was treated at our hospital. The slight dyspnea and the fatigue of both femoral regions appeared in April 2007. He was attended with a dyspnea and pyrexia in May. The chest X-ray and the computed tomography showed ground glass opacity. He was diagnosed with polymyositis (PM) accompanied with interstitial pneumonia (IP) due to clinical findings, the elevation of serum muscle enzymes (creatine kinase, aldolase, myoglobin), the positive test for anti Jo-1antibody,the elevation of KL-6and the depression of O₂ saturation. First, he was treated with methylprednisolone pulse therapy and mechanical ventilation, but the condition of the patient worsened. Thereafter, he was treated with cyclosporine A, cyclophosphamide pulse, high dose intravenous immunoglobulin and plasmapheresis. Finally he died due to respiratory failure. The autopsied lung revealed nonspecific interstitial pneumonia (NSIP). IP accompanied with PM, in general, suggests a pattern of NSIP, and the prognosis of positive cases of anti Jo-1antibody is reported to be good. We report a rare case, which was accompanied with resistant IP following up adenocarcinoma of the prostate and which was subject to both IP and PM at same time.